2019
DOI: 10.5114/aoms.2018.79488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endocan and endoglin levels in chronic kidney disease due to diabetes mellitus

Abstract: IntroductionEndocan and endoglin have been shown to play a role in angiogenesis. Aberrant excessive angiogenesis is a main factor in the development of diabetic nephropathy. In this study we evaluated endocan and endoglin levels in diabetes patients with and without albuminuria and compared them with healthy subjects. Therefore we aimed at gaining a better understanding of the role of angiogenesis in diabetic nephropathy and to assess the predictive role of endocan and endoglin as markers of diabetic nephropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Although several previous studies have shown higher endocan levels in T2D [8,10,11], some others showed the opposite, i.e. lower endocan levels in T2D than in controls [12].…”
Section: Introductionmentioning
confidence: 77%
“…Although several previous studies have shown higher endocan levels in T2D [8,10,11], some others showed the opposite, i.e. lower endocan levels in T2D than in controls [12].…”
Section: Introductionmentioning
confidence: 77%
“…It is known that both diabetics and smoking leads to endothelial dysfunction 3,27 . In the literature, several studies reported that endocan levels were determined to be higher in diabetic patients compared to control groups 27,28 . In our study, we formed the control group from patients who did not smoke and did not have any disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another research group investigated the role of endocan and another glycoprotein, endoglin, in CKD caused by diabetes mellitus [ 20 ]. The study included diabetic patients with and without diabetic nephropathy (DN), and controls.…”
Section: Endocan In Ckdmentioning
confidence: 99%